Mechanisms of γ-glutamylcysteine ligase regulation - Toroser, Dikran; Yarian, Connie S.; Orr, William C.; Sohal, Rajindar S. (Biochimica et biophysica acta, 2006)
The principal objective of this study was to investigate the mechanisms regulating the activity of γ-glutamylcysteine ligase (GCL; EC 6.3.2.2), the rate limiting enzyme in glutathione biosynthesis. Two phylogenetically divergent species, mouse and the fruitfly, Drosophila melanogaster were used to test the hypothesis that reversible protein phosphorylation and pyridine dinucleotide phosphate dependent allostery regulate GCL activity. GCL was almost completely inhibited under phosphorylating conditions, involving preincubations with MgATP and endogenous protein kinases. Maximal GCL inhibitions of 94%, 77%, 85%, 87%, 83%, 95% and 89% occurred, respectively, in mouse cerebellum, hippocampus, brainstem, striatum, cortex and heart, and Drosophila. These changes in GCL activity were detected using saturating levels of substrates, suggesting that V max was dramatically affected, whereas K m values showed no differences. In vitro activation of GCL, presumably due to dephosphorylation, was blocked by inhibitors of protein phosphatases, suggesting that GCL exists in vivo as a mixture of phosphorylated and dephosphorylated forms. The reversibility of the dephosphorylation-dependent activation was indicated by the time-dependent inactivation of the in vitro activated Drosophila GCL, by preincubation with MgATP. NADPH increased maximal GCL activity by up to 93%, whereas several other nucleotide analogues did not, thereby demonstrating specificity. Kinetic analysis using Hanes–Woolf replots of initial velocity data suggested that the NADPH-dependent stimulation of GCL activity is brought about by a change in the maximal activity, V max, rather than changes in substrate affinity. Results of this study suggest that mechanisms of modulation of eukaryotic GCL enzymes may include specific binding of ligands such as pyridine dinucleotide phosphates and reversible protein phosphorylation.